DISKRIMINASI GENDER DALAM FILM “YUNI” (ANALISIS SEMIOTIKA ROLAND BARTHES) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This research focuses on gender discrimination in the film "Yuni" with the aim of (1) Finding out the meaning of the denotation and connotation of gender discrimination contained in the film "Yuni". (2) To find out the form of representation of gender discrimination in the film "Yuni".This research uses qualitative methods with semiotic analysis in order to make it easier to analyze symbols/signs in films. Data collection was carried out by watching the film "Yuni" and conducting documentation as research material, then analyzing data from the footage that had been collected using the semiotics model of Roland Barthes. The results showed that in the film "Yuni" there are several forms of gender discrimination experienced by women. The gender discrimination that occurs in this film is largely influenced by the thick patriarchal culture in Indonesian social life, especially in rural areas. The form of gender discrimination representation contained in Yuni is divided into five actions, namely stereotypes, marginalization, subordination, physical violence, and psychological violence. In addition, there are also two forms of behavior that can be categorized as gender discrimination, namely linking between virginity and morals, female stigma, and sexuality.